Determinants of quality contraceptive counselling information among young women in Sierra Leone: insights from the 2019 Sierra Leone demographic health survey - Quraish Sserwanja; Lilian Nuwabaine; Kassim Kamara; Milton W. Musaba (BMC, 2023)
Abstract Background The quality of contraceptive counseling information received by prospective clients of family planning services can greatly influence both the uptake and continued use of contraceptives. Therefore, an understanding of the level and determinants of quality contraception information among young women in Sierra Leon could inform family programs, with the aim of reducing the high unmet need in the country. Methods We analyzed secondary data from the 2019 Sierra Leone Demographic Health Survey (SLDHS). Participants were young women aged 15-24 years, who were using a family planning method (n = 1,506). Good quality family planning counselling was defined a composite variable that included; a woman being told about side effects, how to deal with side effects, and the availability of other family planning methods/options. Logistic regression was performed using SPSS software version 25. Results Out of 1,506 young women, 955 (63.4%, 95% CI: 60.5-65.3) received good quality family planning counselling services. Of the 36.6% that received inadequate counselling, 17.1% received no counselling at all. Good quality family planning counselling services was positively associated with receiving family planning services from government health facilities (aOR: 2.50, 95% CI: 1.83-3.41), having no major challenges with distance to access healthcare (aOR: 1.45, 95% CI: 1.10-1.90), having visited a health facility (AOR: 1.93, 95% CI: 1.45-2.58), and having been visited by a health field worker within the last 12 months (aOR: 1.67, 95% CI: 1.24-2.26) while residing in the southern region ( aOR: 0.39, 95% CI: 0.22-0.69) and belonging to the richest wealth quintile (aOR: 0.49, 95% CI: 0.24-0.98) were associated with less odds of receiving good quality family planning counselling services. Conclusion About 37% of the young women in Sierra Leone do not receive good quality family planning counselling services of which 17.1% received none. Based on the study's findings, it is important to emphasize the need to ensure that all young women have access to proper counselling services especially for those receiving these services from private health units, from the southern region and richest wealth quintile. Ensuring easier access through increasing affordable and friendly access points and strengthening field health workers' capacity in providing family planning services could also help improve access to good quality family planning services.